Energy Storage System (ESS) To Integrate Intermittent Renewable Energy Sources - Dr. N. Malathy,; Raja Yashwanth Sai,; K.Vagdevi,; Dr.J.N.Swaminathan,; Poojitha Mallireddy,; Aasiya.P, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Renewable energy sources generate power in a variable manner, and there may be unacceptably large fluctuations. Therefore, renewable energy is currently stored in batteries or super capacitors for later use, but this requires expensive maintenance. Therefore, the primary goal of the proposed system is to control renewable energy during fluctuations to provide a continuous power supply. To achieve this, we continuously monitor the solar panel's power generation and load usage, and we send these data to a machine learning model to categorize the switching status of the regulator circuit. All of these artificial intelligence processes are carried out on the Python platform.
Keywords: Renewable Energy; Solar Power Generation; Power Regulation Fluctuation Control; Uninterrupted Power Supply; AI in Power Systems; Switching Regulator Circuit; Python for Energy Management; Power Generation Forecasting Smart Grid Energy